2021
DOI: 10.1002/smm2.1032
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nanocomposites consisting of Pt3Co alloy particles and CoP2 nanorods towards high‐efficiency methanol electro‐oxidation

Abstract: Heterogeneous nanocomposites comprising chemically distinct constituents are particularly promising in electrocatalysis. We herein report a synthetic strategy that combines the reduction of Pt and Co ionic precursors at an appropriate ratio with the subsequent phosphating at an elevated temperature for forming heterogeneous nanocomposites consisting of quasi‐spherical Pt3Co alloy domains and rod‐like CoP2 domains for high‐efficiency methanol electro‐oxidation. The strong electronic coupling between Pt3Co and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…To address these bottlenecks, various materials as favorable photoanode, such as TiO 2 , BiVO 4 , WO 3 , Fe 2 O 3 , TaON, Ta 3 N 5 , GaP, etc., have attracted more attention for PEC water splitting. Among different photoanodes, BiVO 4 has been shown to be one of the most promising candidates due to its suitable bandgap and low cost. , However, the PEC performance is restrained by the poor charge transport and serious photocorrosion of BiVO 4 photoanode. , Consequently, extensive efforts have been devoted to addressing the limitations by morphology engineering, heterojunction construction, and surface modification. Thus, it is inevitable to rationally design excellent and stable BiVO 4 photoanode by effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…To address these bottlenecks, various materials as favorable photoanode, such as TiO 2 , BiVO 4 , WO 3 , Fe 2 O 3 , TaON, Ta 3 N 5 , GaP, etc., have attracted more attention for PEC water splitting. Among different photoanodes, BiVO 4 has been shown to be one of the most promising candidates due to its suitable bandgap and low cost. , However, the PEC performance is restrained by the poor charge transport and serious photocorrosion of BiVO 4 photoanode. , Consequently, extensive efforts have been devoted to addressing the limitations by morphology engineering, heterojunction construction, and surface modification. Thus, it is inevitable to rationally design excellent and stable BiVO 4 photoanode by effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain an in‐depth understanding of the roles of MQD and MoO x for the oxygen evolution reaction activity and comprehend the mechanism for these highly efficient photoelectrodes, we performed density functional theory calculations based on the correlative theoretical models of BiVO 4 , MQD/BiVO 4 and MoO x /MQD/BiVO 4 , as shown in Figure 6a and Figure S36–S38. Four elementary reaction steps are involved in the OER process and these include different intermediates (*OH, *O and *OOH, * denotes the active sites of the catalyst) [53–56] . According to the calculation results, a big energy barrier ( η ) of 1.40 eV (Figure 6b) was obtained for the pristine BiVO 4 with the formation of *OH as the potential rate‐determining step (RDS).…”
Section: Resultsmentioning
confidence: 98%
“…50 The lattice-mismatch strain in the core-shell structures can improve their electrocatalytic activity toward the MOR. 39,50,51,64,65 Moreover, some crystal defects like twins are observed in the Ru fcc @Pt NSs, which might enhance the MOR performance. Third, in our work, it was found that the Ru NS core can modulate the electronic structure of the ultrathin Pt shell, as proved by the aforementioned XPS results (Fig.…”
Section: Resultsmentioning
confidence: 99%